German Inbound Investment, Corporate Tax Planning, and Thin-Capitalization Rules - A Difference-in-Differences Approach - Michael Overesch; Georg Wamser (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2006)
This paper investigates tax planning behavior by means of inter-company finance and the effectiveness of fighting back via thin-capitalization rules. A simple theoretical model, which considers the financing decision of a multinational company, is used to obtain empirical implications. The empirical analysis, based on German inbound investment data from 1996 until 2004, supports a significant impact of tax rate differences on the use of intra-company debt. The effectiveness of the German thin-capitalization rule is tested by using legal amendments as natural experiments. The results suggest that the German thin-capitalization rule induces significantly lower intra-firm debt-levels of inbound investments. Hence, tax planning via intra-firm finance is effectively limited.
Keywords: G32; H25; H26; 330; Corporate income tax; multinationals; thin-capitalization rule; difference-indifferences; firm-level data